Determinan Bias Boundary dan Bias Pengambilan Keputusan: Perspektif Bounded Rationality Theory - Rita Yuliana; Hanif Yusuf Seputro; Tito IM. Rahman Hakim (Universitas Trunojoyo Madura, 2020)
In accounting, decision is an important aspect but prone to bias in its making process. Limitation in decision making that lead to bias is driven by some bound. This study aims to enunciate some bounds and identify bias determinant in decision making process. Literature review is employed to analyze thirty-four articles since 1986 until 2018 from renown journal publisher such as science direct, emerald, Jstor regarding decision making in business field. The results shows that there are 9 bias determinant in decision making process such as task complexity, information presentation format, quality and quantity of information/data, situation/environment, competency, method, experience, personality trait and motivation. This article contribute to body of literature and decision makers by provide gap on decision making on the context of judgment bias and bias determinant that should take in to account before making a decision for better result.